The impact of social support, husband-wife interactions, and religious belief on subjective well-being of Malay families - Syamila Karunia; Euis Sunarti; Tin Herawati (Center for Sociological Studies and Community Developmen, 2026)
This study fills a gap in the literature by examining how social support, husband wife interaction, and religiosity collectively shape subjective family well-being among Malay families in Indonesia. The study employs an explanatory quantitative design, with data collected from 149 respondents in Tebing Tinggi Okura, Pekanbaru, Riau, through structured interviews using probing techniques guided by a standardized questionnaire, including the Sarafino and Cubbin instruments modified by Sunarti et al., as well as the Aksi-Ga, Religius-Ga, and Tera-Ga instruments developed by Sunarti. Data were analyzed using descriptive statistics, correlation analysis, and structural equation modeling–partial least squares (SEM-PLS). The results indicate that social support falls into the low category, husband wife interaction into the moderate category, and religiosity and family subjective well-being into the high category. Social support, husband wife interaction, and religiosity have a positive and significant effect on subjective well-being, both directly and indirectly. Although income levels are relatively low, most families are able to maintain high subjective well-being through strong religious involvement and harmonious marital relationships. These findings confirm that family subjective well-being is determined not only by economic conditions but also by psychosocial factors, including social support, husband wife interaction, and religiosity.